2010
DOI: 10.1017/s0022377810000024
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear modulation of ion-acoustic waves in two-electron-temperature plasmas

Abstract: The amplitude modulation of ion-acoustic waves is investigated in a plasma consisting of adiabatic warm ions, and two different populations of thermal electrons at different temperatures. The fluid equations are reduced to nonlinear Schrödinger equation by employing a multi-scale perturbation technique. A linear stability analysis for the wave packet amplitude reveals that long wavelengths are always stable, while modulational instability sets in for shorter wavelengths. It is shown that increasing the value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Let us consider the propagation of dust-acoustic (DA) waves in a magnetic field pointing to the z-direction in presence of negatively charged mobile dust, ions of temperature T i (following Maxwellian distribution) and two distinct temperature electrons (following nonextensive q-distribution each) of temperature T e1 and T e2 , existing in space and laboratory plasma system both experimentally (Schippers et al 2008;Jones et al 1975) and theoretically (Shamansouri and Alinejad 2013;Esfanyari-Kalijahi et al 2010;Masood et al 2009;Saini and Shalini 2013;Baluku and Hellberg 2012;Sultana et al 2012). We assume that T e2 T e1 T i , so that at equilibrium the quasi-neutrality condition requires n i0 = n e10 + n e20 + Z d n d0 , or μ i = μ 1 + μ 2 + 1, where n e10 , n e20 , n i0 and n d0 are respectively, the densities of cold electrons, hot electrons, ions and dust at equilibrium.…”
Section: Modeling Equationsmentioning
confidence: 99%
“…Let us consider the propagation of dust-acoustic (DA) waves in a magnetic field pointing to the z-direction in presence of negatively charged mobile dust, ions of temperature T i (following Maxwellian distribution) and two distinct temperature electrons (following nonextensive q-distribution each) of temperature T e1 and T e2 , existing in space and laboratory plasma system both experimentally (Schippers et al 2008;Jones et al 1975) and theoretically (Shamansouri and Alinejad 2013;Esfanyari-Kalijahi et al 2010;Masood et al 2009;Saini and Shalini 2013;Baluku and Hellberg 2012;Sultana et al 2012). We assume that T e2 T e1 T i , so that at equilibrium the quasi-neutrality condition requires n i0 = n e10 + n e20 + Z d n d0 , or μ i = μ 1 + μ 2 + 1, where n e10 , n e20 , n i0 and n d0 are respectively, the densities of cold electrons, hot electrons, ions and dust at equilibrium.…”
Section: Modeling Equationsmentioning
confidence: 99%
“…The ultimate consequence of the balance occurring between the non-linearities and the wave group dispersion is called an envelope soliton. The oblique MI of IA waves in a collisionless unmagnetized plasma containing two distinct temperature isothermal electrons have been studied in refs [34,35]. [11][12][13][14][15][16] The KdV soliton is formed when wave phase dispersion balances the non-linearity of the medium.…”
Section: Introductionmentioning
confidence: 99%
“…The modulational instability of IA waves in multi-species unmagnetized or magnetized plasmas have been studied by a number of authors theoretically [10,[24][25][26][27][28][29][30] and experimentally [31,32] Kourakis and Shukla [33] investigated the MI of IA waves in a collisionless unmagnetized plasma with oblique propagation, comprising of cold ions and two distinct populations of isothermal electrons at different temperatures. The oblique MI of IA waves in a collisionless unmagnetized plasma containing two distinct temperature isothermal electrons have been studied in refs [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of the formation of double layers in twoelectron-temperature plasmas has also been studied in detail by various authors [19,20]. Recently, Esfandyari-Kalejahi et al [22] studied the nonlinear modulation of ionacoustic waves (IAWs) in a two-electron-temperature plasma and found that the increasing hot-to-cold electron ratio favored the growth of modulational instability. Recently, Esfandyari-Kalejahi et al [22] studied the nonlinear modulation of ionacoustic waves (IAWs) in a two-electron-temperature plasma and found that the increasing hot-to-cold electron ratio favored the growth of modulational instability.…”
Section: Introductionmentioning
confidence: 99%
“…Masood et al [21] studied the propagation of ion-acoustic solitons in a twoelectron-temperature plasma in cylindrical and spherical geometries and showed that an increase in the ratio of hot-to-cold electron temperature decreases the rarefactive solitary potential. Recently, Esfandyari-Kalejahi et al [22] studied the nonlinear modulation of ionacoustic waves (IAWs) in a two-electron-temperature plasma and found that the increasing hot-to-cold electron ratio favored the growth of modulational instability. More recently, Balaku et al [23] revisited IAWs in a twotemperature plasma and found that positive-potential double layers can form below a critical density ratio, associated with the third derivative of the Sagdeev potential evaluated at the origin for the phase velocity of the linear wave.…”
Section: Introductionmentioning
confidence: 99%